2017
DOI: 10.3748/wjg.v23.i30.5610
|View full text |Cite
|
Sign up to set email alerts
|

Incidents and adverse events of endoscopic ultrasound-guided fine-needle aspiration for pancreatic cystic lesions

Abstract: AIMTo evaluate the diagnostic value and safety mainly regarding incidents of endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) for pancreatic cystic lesions (PCLs).METHODSA total of 150 consecutive patients with suspected PCLs were prospectively enrolled from April 2015 to November 2016. We finally enrolled 140 patients undergoing EUS-FNA. We compared the diagnostic accuracy of EUS-FNA and pathological diagnosis, which is regarded as the gold standard, for PCLs. Patients undergoing EUS-FNA at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
(48 reference statements)
1
11
0
Order By: Relevance
“…5-8,29-31 However, the negative predictive value of EUS-FNA was relatively low at 50%, which was reported to be 50.9%-85.2% in similar studies. 5,7,30,31 Hence, if a pancreatic lesion has high clinical suspicion of malignancy while the EUS-FNA was negative, other investigations should be offered as part of the workup for malignancy or repeat EUS-FNA should be performed as another attempt for pathological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…5-8,29-31 However, the negative predictive value of EUS-FNA was relatively low at 50%, which was reported to be 50.9%-85.2% in similar studies. 5,7,30,31 Hence, if a pancreatic lesion has high clinical suspicion of malignancy while the EUS-FNA was negative, other investigations should be offered as part of the workup for malignancy or repeat EUS-FNA should be performed as another attempt for pathological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…32 They also however reported that 1.7% of patients had an adverse event which interfered with the planned treatment and 37.9% had an incident with signs and symptoms that did not affect the planned treatment. 32 A meta-analysis on the diagnostic accuracy of EUS-FNA cytology has concluded that it had a pooled sensitivity of 63% and a specificity of 88%. 33 The low sensitivity may be explained by the limited numbers and poor quality of aspirated epithelial cells in cyst fluid obtained for cytology.…”
Section: American College Of Gastroenterology (Acg) Guidelinesmentioning
confidence: 98%
“…It facilitates in vivo microscopy during endoscopic procedures and there is increasing interest in the use of CLE in the diagnosis of biliary strictures and PCLs. 32 CLE allows real-time evaluation of histology with highresolution imaging (1-3.5 μm) without the need for a biopsy and can be used with both ERCP catheters (CholangioFlex probe, Paris, France) and EUS-FNA needles (AQ-Flex 19 probe) 37,38 which at present are manufactured by Cellvisio, Mauna Kea Technologies, Paris, France. 38 As well as real-time use, there is also the benefit of post-procedure review of imaging videos with the ability to play and pause and also measure structure s of interest.…”
Section: Needle-based Confocal Laser Endomicroscopymentioning
confidence: 99%
See 2 more Smart Citations